1999
DOI: 10.1021/bi991696f
|View full text |Cite
|
Sign up to set email alerts
|

ADP-Binding Site of Escherichia coli Succinyl-CoA Synthetase Revealed by X-ray Crystallography,

Abstract: Succinyl-CoA synthetase (SCS) catalyzes the following reversible reaction via a phosphorylated histidine intermediate (His 246alpha): succinyl-CoA + P(i) + NDP <--> succinate + CoA + NTP (N denotes adenosine or guanosine). To determine the structure of the enzyme with nucleotide bound, crystals of phosphorylated Escherichia coli SCS were soaked in successive experiments adopting progressive strategies. In the first experiment, 1 mM ADP (>15 x K(d)) was added; Mg(2+) ions were omitted to preclude the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 32 publications
0
60
0
Order By: Relevance
“…The movement of the phosphohistidine loop with phosphorylated catalytic histidine has been suggested to shuttle the phosphate between the active sites of both subunits. 14,15 The missing fragment in the case of skipping of exon 6 and part of exon 7, encompassing residues 221-267, contains Glu256, a critical residue for ADP phosphorylation. 21 Location of Asp333, a part of 'power' helix b and the interface between subunits, within the modeled human mitochondrial SCS-A (b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The movement of the phosphohistidine loop with phosphorylated catalytic histidine has been suggested to shuttle the phosphate between the active sites of both subunits. 14,15 The missing fragment in the case of skipping of exon 6 and part of exon 7, encompassing residues 221-267, contains Glu256, a critical residue for ADP phosphorylation. 21 Location of Asp333, a part of 'power' helix b and the interface between subunits, within the modeled human mitochondrial SCS-A (b).…”
Section: Discussionmentioning
confidence: 99%
“…(Figure 3; PDB id 1CQI). 15 The protein model indicated the organization of the SCS-A, with ATP-and succinylCoA-binding sites located on the opposite sides of the heterodimer (Figure 3a). We mapped all the known SUCLA2 mutations into the protein model.…”
Section: Quantification Of Mtdnamentioning
confidence: 99%
“…In the case of CoA thioester formation by SCS Ec , the ␥-phosphate of ATP is first transferred to the catalytic His 246 residue in the ␣-subunit, and the phosphorylated imidazole ring reacts with acid and CoA to form the corresponding acyl-CoA molecule. The ATP-and CoA-binding sites are located within the ATP-grasp fold domain in the ␤-subunit (domains 3-4) and the CoA-binding domain in the ␣-subunit (domain 1), respectively (23,27,30,31). The catalytic His residue (corresponding to His 261 in the TK1880 ␣-subunit) and several important residues that function in binding with the ATP⅐Mg 2ϩ complex and CoA are well conserved among this superfamily (18).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon, termed "domain shuffling," is one of the key features of this superfamily (8). Superposition of several structures of SCS from Escherichia coli (ecSCS) (12)(13)(14), Thermus aquaticus (15), the mammalian GTP-specific SCS from pig (16), and a truncated form of human ACLY (17,18) revealed that subdomains 1-5 share a common arrangement in these enzymes. From detailed studies of the reaction mechanism of ecSCS, a crucial enzyme tightly connected to the TCA cycle, a three-step mechanism was proposed, which involves the phosphorylation of a highly conserved His residue at the first active site (site I) as an intermediate step (12,13).…”
mentioning
confidence: 99%
“…Subsequently, the phosphoryl moiety is transferred onto an NDP that is bound at the second active site (site II). The distance of around 36 Å between site I and site II is assumed to be bridged by a so-called "swinging loop" (12,14,19). A mechanism comparable to the mechanism of the SCSs was presumed for the ACDs (20).…”
mentioning
confidence: 99%